Negotiating nursing - Brooks, Jane (Manchester University Press, 2019)
Negotiating nursing explores how the Queen Alexandra's Imperial Military Nursing Service (Q.A.s) salvaged men within the sensitive gender negotiations of what should and could constitute nursing work and where that work could occur. The book argues that the Q.A.s, an entirely female force during the Second World War, were essential to recovering men physically, emotionally and spiritually from the battlefield and for the war, despite concerns about their presence on the frontline. The book maps the developments in nurses' work as the Q.A.s created a legitimate space for themselves in war zones and established nurses' position as the expert at the bedside. Using a range of personal testimony the book demonstrates how the exigencies of war demanded nurses alter the methods of nursing practice and the professional boundaries in which they had traditionally worked, in order to care for their soldier-patients in the challenging environments of a war zone. Although they may have transformed practice, their position in war was highly gendered and it was gender in the post-war era that prevented their considerable skills from being transferred to the new welfare state, as the women of Britain were returned to the home and hearth. The aftermath of war may therefore have augured professional disappointment for some nursing sisters, yet their contribution to nursing knowledge and practice was, and remains, significant.